Expression of Embryonic Stem Cell Markers on the Microvessels of WHO Grade I Meningioma - Shivapathasundram, Ganeshwaran; Wickremesekera, Agadha C.; Brasch, Helen D.; Marsh, Reginald; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2018)
Aim: The presence of cells within meningioma (MG) that express embryonic stem cell (ESC) markers has been previously reported. However, the precise location of these cells has yet to be determined. Methods: 3,3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining was performed on 11 WHO grade 1 MG tissue samples for the expression of the ESC markers OCT4, NANOG, SOX2, KLF4 and c-MYC. Immunofluorescence (IF) IHC staining was performed to investigate localization of each of these ESC markers. NanoString and colorimetric in situ hybridization (CISH) mRNA expression analyses were performed on six snap-frozen MG tissue samples to confirm transcriptional activation of these proteins, respectively. Results: DAB IHC staining demonstrated expression of OCT4, NANOG, SOX2, KLF4 and c-MYC within all 11 MG tissue samples. IF IHC staining demonstrated the expression of the ESC markers OCT4, NANOG, SOX2, KLF4 and c-MYC on both the endothelial and pericyte layers of the microvessels. NanoString and CISH mRNA analyses confirmed transcription activation of these ESC markers. Conclusion: This novel finding of the expression of all aforementioned ESC markers in WHO grade 1 MG infers the presence of a putative stem cells population which may give rise to MG.